Effect of Kangaroo Mother Care on Postpartum Depression - Abbasyan Azar, fatemeh; ahmadi, mahbobeh; shams, jamal; abadi, alireza (Advances in Nursing & Midwifery, 2013)
Abstract Background and aim: The maternity blues is the most common postnatal mood disturbance.The purpose of this study was to assess the effect of kangaroo mother care on maternity blues Material and Methods. A clinical trial was conducted to assess the effect of kangaroo mother care on maternity blues. The sample of the study consisted of 96 pregnant women with gestational age 37 -42 weeks, which were assigned to intervention and control groups. The mothers in intervention group provided kangaroo care for 10 consecutive days. Data were collected by Beck depression scale, General Helth Qustioner, , Stein's Blues Scale Vinfild and Tighmen’s social support scale and Peghle’s adverse life events scle . Maternal blues was measured at the 1st -3rd -5th and 10th days during the study. Data were analyzed by SPSS statistical software. Findings: Results of the study showed higher scores of maternal blues in the control group. There was a significant diference between the maternal blues scores of the intervention and control group at 3rd ,5th and 10th days of the study( P<o.o5). The results showed a significant correlation between the numbers and durations of kangaroo care and maternal blues scale. The results suggest the positive effect of kangaroo mother care on reducing the post -partum blues among mothers . Conclusion: This study shows the positive effect of kangaroo mother care on maternal blues Key words: maternal blues-skin to skin contact- Kangaroo mother care